2021
DOI: 10.3390/rs13214356
|View full text |Cite
|
Sign up to set email alerts
|

A ROTI-Aided Equatorial Plasma Bubbles Detection Method

Abstract: In this study, we present a Rate of Total Electron Content Index (ROTI)-aided equatorial plasma bubbles (EPBs) detection method based on a Global Navigation Satellite System (GNSS) ionospheric Total Electron Content (TEC). This technique seeks the EPBs occurrence time according to the ROTI values and then extracts the detrended ionospheric TEC series, which include EPBs signals using a low-order, partial polynomial fitting strategy. The EPBs over the Hong Kong area during the year of 2014 were detected using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
3
5
0
Order By: Relevance
“…The latitudinal and temporal variations of EPB during 2014 observed by Jason-2 vTEC data are consistent to those of other measurements such as in situ satellite data (Aa et al, 2020) and GNSS TEC (Tang et al, 2021) reported in previous studies, suggesting the observed EPB events are reliable. In addition, obviously, the R-T instability mechanism is also suitable to explain the latitudinal and temporal variations of EPB.…”
Section: Resultssupporting
confidence: 91%
“…The latitudinal and temporal variations of EPB during 2014 observed by Jason-2 vTEC data are consistent to those of other measurements such as in situ satellite data (Aa et al, 2020) and GNSS TEC (Tang et al, 2021) reported in previous studies, suggesting the observed EPB events are reliable. In addition, obviously, the R-T instability mechanism is also suitable to explain the latitudinal and temporal variations of EPB.…”
Section: Resultssupporting
confidence: 91%
“…In Figure 1, the highest values are mostly in the nighttime and between 0.07-0.2 TECu; this indicates that a scintillation is often a nighttime event. This is coherent with Tang et al [31] and Ji et al [26] who have shown that a greater percentage of ROTI lies between 0.02 and 0.05 TECu in the Hong Kong region. In this present study, the ROTI avg threshold is set at 0.075 TECu instead of 0.8 TECu, unlike Oladipo et al [33] but the same as Nishioka et al [36], who suggested a scintillation threshold of 0.075 TECu in the Asian region.…”
Section: Resultssupporting
confidence: 90%
“…Finally, at five-minute intervals of the rate of TEC (ROT), ROTI was computed according to Equation (2), where ROT and ROTI are in TEC units (TECu: 1 TECu = 10 16 e/m 2 ) and the notation • is the averaging operation [31].…”
Section: Rotimentioning
confidence: 99%
“…When the generalized likelihood ratio test is used, the decision threshold is calculated according to (9), and the test statistic is constructed according to (10), where the false alarm probability and the missing alarm probability are both taken as 10 -3 . The detection results on January 1 and March 17 are shown in Fig.…”
Section: Analysis Of Detection Resultsmentioning
confidence: 99%
“…Previous studies have shown that ROTI is an effective index for detecting ionospheric anomalies in time domain [10], which can be used to verify the performance of GLRT, and it can be calculated as follows:…”
Section: Rate Of Tec Change Indexmentioning
confidence: 99%